Avelumab plus axitinib versus sunitinib in advanced renal cell carcinoma: biomarker analysis of the phase 3 JAVELIN Renal 101 trial - Motzer, Robert J.; Robbins, Paul B.; Powles, Thomas; Albiges, Laurence; Haanen, John B.; Larkin, James; Mu, Xinmeng Jasmine; Ching, Keith A.; Uemura, Motohide; Pal, Sumanta K.; Alekseev, Boris; Gravis, Gwenaelle; et al. (Nature medicine, 2020)
We report on molecular analyses of baseline tumor samples from the phase 3 JAVELIN Renal 101 trial ( n = 886; NCT02684006 ), which demonstrated significantly prolonged progression-free survival (PFS) with first-line avelumab + axitinib versus sunitinib in advanced renal cell carcinoma (aRCC). We found that neither expression of the commonly assessed biomarker programmed cell death ligand 1 (PD-L1) nor tumor mutational burden differentiated PFS in either study arm. Similarly, the presence of FcɣR single nucleotide polymorphisms was unimpactful. We identified important biological features associated with differential PFS between the treatment arms, including new immunomodulatory and angiogenesis gene expression signatures (GESs), previously undescribed mutational profiles and their corresponding GESs, and several HLA types. These findings provide insight into the determinants of response to combined PD-1/PD-L1 and angiogenic pathway inhibition and may aid in the development of strategies for improved patient care in aRCC. Biomarker analysis of the phase 3 JAVELIN Renal 101 trial uncovers molecular determinants of therapy-specific outcomes, which may inform personalized treatment strategies for patients with advanced renal cell carcinoma.